Audio steganography using least significant bit and AES cryptographic algorithm / Nurul Hidayah Ahmad Zukri ... [et al.] - Ahmad Zukri, Nurul Hidayah; Kamarudin, Nur Khairani; Izraf Ishak, Mohd Enif; Md Rashid, Nor Aimuni (Universiti Teknologi MARA Cawangan Pulau Pinang, 2018)
In the era of technology, massive amount of data have been stored and exchanged over the internet. One of the most important factors of data communication has been the security of the credential information. Cryptography is a technique for securing the secrecy of the information. Many different techniques have been developed under the cryptography umbrella. However, it is not enough to keep the contents of a message secret. Thus, another algorithm should be implemented to keep the existence of a message secret. Steganography is an interesting and effective method for concealing data throughout the history. In this paper, Least Significant Bit (LSB) algorithm has been proposed. This algorithm can help users to protect their confidential information during transmission by embedding the data inside the audio .wav file. This application implements an Advance Encryption Standard (AES) to enhance the steganography security by encrypting the information and as such, only the intended recipient can read the data. The proposed method is analyzed in terms of audio similarity analysis between the original file and the audio steganography file. The result shows about 100% of similarity between both files. File integrity is also measured and the results show the hashing value of the encrypted file was different compared to the original file